High-Speed Adaptive Waveform Generation System for Multi-Material Surface Printing - Qiuming Luo; Yanming Lei; Kunzhong Wu; Xuan Wei (Chips)
This paper presents an FPGA-based configurable drive waveform generation system for industrial inkjet printheads, targeting the need for real-time adaptability in printing across heterogeneous materials. The system adopts a three-array waveform description method, enabling flexible configuration and precise generation of drive waveforms with adjustable geometry, segment duration, and voltage levels. Through a modular and parameterized design, the system supports rapid waveform switching during column-wise printing without interrupting the printing process, addressing the challenges posed by varying ink absorption characteristics across different substrates. Experimental results demonstrate the system’s capability to achieve smooth waveform transitions within an interval of 830 µs between columns, with data loading times as low as 4 µs. This efficient performance ensures seamless operation and high flexibility. The proposed approach significantly reduces the hardware cost and improves printing efficiency, offering a scalable and robust solution for next-generation industrial inkjet applications involving complex and dynamic material surfaces.